2001
DOI: 10.1164/ajrccm.164.3.2008149
|View full text |Cite
|
Sign up to set email alerts
|

Oral Clearance and Pathogenic Oropharyngeal Colonization in the Elderly

Abstract: The elderly have an increased incidence of oropharyngeal colonization with respiratory pathogens, a well-known risk factor for the development of pneumonia. Changes in the oral milieu may occur secondary to decreased salivary production and abnormalities in swallowing. These abnormalities, common in the elderly, may result in impaired clearance of organisms, allowing pathogenic colonization. To test this hypothesis, we performed a prospective cross-sectional analysis of 75 elderly institutionalized patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(67 citation statements)
references
References 15 publications
2
60
0
5
Order By: Relevance
“…The aspiration of small amounts of oropharyngeal secretions during sleep is a common finding in older adults [22,23] and usually happens without consequences due to preserved cough reflex, ciliary transport and immune system and to the low virulence of normal pharyngeal flora. However, the silent aspiration of large amounts during swallowing is an abnormal and serious finding that, together with several factors common in the elderly such as progressive decrease in pulmonary function, decline in host defences, impaired cough reflex and increased oropharyngeal colonisation with respiratory pathogens can lead to aspiration pneumonia [19]. A key point of our study is that we elucidated the pathogenic mechanism of the aspiration process and impaired airway protection of patients with CAP through videofluoroscopy.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The aspiration of small amounts of oropharyngeal secretions during sleep is a common finding in older adults [22,23] and usually happens without consequences due to preserved cough reflex, ciliary transport and immune system and to the low virulence of normal pharyngeal flora. However, the silent aspiration of large amounts during swallowing is an abnormal and serious finding that, together with several factors common in the elderly such as progressive decrease in pulmonary function, decline in host defences, impaired cough reflex and increased oropharyngeal colonisation with respiratory pathogens can lead to aspiration pneumonia [19]. A key point of our study is that we elucidated the pathogenic mechanism of the aspiration process and impaired airway protection of patients with CAP through videofluoroscopy.…”
Section: Discussionmentioning
confidence: 92%
“…***: p,0.001. pulmonary or oropharyngeal pathogens may colonise the oropharynx and be a potential source of pulmonary infections [19]. TERAMOTO et al [20] reported that the prevalence of aspiration pneumonia in patients with CAP aged o70 years was 60.1%, using a wide variety of clinical assessment methods.…”
Section: Discussionmentioning
confidence: 99%
“…Antibacterial immunity is impaired in the elderly due to complex changes in innate and adaptive immunity called immunosenescence (63)(64)(65).…”
Section: Discussionmentioning
confidence: 99%
“…The prevention of VAP reduces the duration of mechanical ventilation, length of hospital stay, mortality, and healthcare costs (10). Another preventive method in patients undergoing mechanical ventilation is raising HOB to 30 degrees or more (11). According to clinical guidelines related to the prevention of pneumonia and aspiration, HOB should be elevated to 30 -45 degrees among mechanically ventilated patients (12).…”
Section: Introductionmentioning
confidence: 99%